2019
DOI: 10.1177/0143624419842006
|View full text |Cite
|
Sign up to set email alerts
|

Overheating risk in Passivhaus dwellings

Abstract: Highly insulated and airtight homes designed to reduce energy consumption are perceived as having a greater summer overheating risk than less insulated homes. If true, dwellings built to the well-known low-energy Passivhaus (PH) standard could be at greatest risk due to the use of superinsulation, especially as the climate warms. Existing studies are inconclusive and even contradictory, mainly due to small sample sizes. Hence, this paper presents the first large-scale overheating risk analysis of UK Passivhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…There is a varied body of research on overheating in residential buildings in Europe [5][6][7][8][9][10][11][12][13][14][15][16]. In [16], there is a wide sample of these studies focusing on buildings with Passivhaus certificate dating 2011 to 2015.…”
Section: Relevant Previous Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a varied body of research on overheating in residential buildings in Europe [5][6][7][8][9][10][11][12][13][14][15][16]. In [16], there is a wide sample of these studies focusing on buildings with Passivhaus certificate dating 2011 to 2015.…”
Section: Relevant Previous Case Studiesmentioning
confidence: 99%
“…Overheating is a known problem in highly airtight and insulated buildings with numerous studies confirming it [5][6][7][8][9] and analysing energy efficiency and comfort in a variety of European climates. A common element in these studies is that occupants are often more satisfied with winter comfort than summer comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell et al [9] did analysis on the overheating risk in passive dwellings. It was found that in highly insulated dwellings overheating should be considered for individual rooms rather than at whole-dwelling level.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally designed for cold climates, but a consolidated body of research has already investigated its suitability and applicability in temperate and warm climates [30,32]. However, even highly insulated and airtight Passivhaus buildings with active ventilation can face a summer overheating risk [33]. Therefore, optimisation of several design inputs for Passivhaus buildings, including external shading devices, thermal mass effect and glazing ratios are becoming increasingly relevant to prevent summer overheating even in mild climates [34].…”
Section: Envelope Optimisationmentioning
confidence: 99%